The Arbuscular Mycorrhizal Fungus Rhizophagus irregularis MUCL 41833 Modulates Metabolites Production of Anchusa officinalis L. Under Semi-Hydroponic Cultivation - Cartabia, Annalisa; Tsiokanos, Evangelia; Tsafantakis, Nikolaos; Lalaymia, Ismahen; Termentzi, Aikaterini; Miguel, Maria; Fokialakis, Nikolas; Declerck, Stéphane (Frontiers in Plant Science, 2021)
Anchusa officinalis is recognized for its therapeutic properties which are attributed to the production of different metabolites. This plant interacts with various microorganisms including the root symbiotic arbuscular mycorrhizal fungi (AMF). Whether these fungi play a role in the metabolism of A. officinalis is unknown. In the present study, two independent experiments, associating A. officinalis to the AMF Rhizophagus irregularis MUCL 41833, were conducted in a semi-hydroponic (S-H) cultivation system. The experiments were intended to investigate the primary and secondary metabolites (PMs and SMs, respectively) content of shoots, roots and exudates of mycorrhized (M) and non-mycorrhized (NM) plants grown 9 (Exp. 1) or 30 (Exp. 2) days in the S-H cultivation system. Differences in the PMs and SMs were evaluated by an untargeted ultrahigh-performance liquid chromatography high-resolution mass spectrometry metabolomics approach combined with multivariate data analysis. Differences in metabolites production were shown in Exp. 1. Volcano-plots analysis revealed a strong up-regulation of 10 PMs and 23 SMs. Conversely, in Exp. 2, no significant differences in PMs and SMs were found in shoots or roots between M and NM plants with the exception of the coumarin scoparone and the furanocoumarin byakangelicin, accumulated in the exudates of the M plants. In Exp. 1 we noticed an enhanced production of PMs, including organic acids and amino acids, with the potential to act as precursors of other amino acids and as building blocks for the production of macromolecules. Similarly, SMs production was significantly affected in Exp 1. In particular the phenolic compounds derived from the phenylpropanoid pathway. Fifteen di-, tri- and tetra- meric C6-C3 derivatives of caffeic acid were induced mainly in the roots of M plants, while 4 oleanane-types saponins were accumulated in the shoots of M plants. Two new salvianolic acid B derivatives and one new rosmarinic acid derivative, all presenting a common substitution pattern (methylation at C-9’’’ and C-9’ and hydroxylation at C-8), were detected in the roots of M plants. The accumulation of diverse compounds observed in colonized plants suggested that AMF have the potential to affect specific plant biosynthetic pathways.